Propositions relatives et niveau phrastique - Gérard Melis (Anglophonia)
The purpose of this paper is to analyse various cases of so-called “appositive relative clauses” in an enunciative textual perspective. Briefly discussing the current terminology, it explores the distinction between “attached relative clauses” and “detached relative clauses”, concentrating on the second case. Its main purpose is to underline the fact that such clauses have a role to play not only at the level of the NP but also - and mainly- at the level of the complete utterance, involving referential, textual and subjective parameters.